2016
DOI: 10.1007/s11219-016-9324-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality in model-driven engineering: a tertiary study

Abstract: Model-driven engineering (MDE) is believed to have a significant impact in software quality. However, researchers and practitioners may have a hard time locating consolidated evidence on this impact, as the available information is scattered in several different publications. Our goal is to aggregate consolidated findings on quality in MDE, facilitating the work of researchers and practitioners in learning about the coverage and main findings of existing work as well as identifying relatively unexplored niches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Maintainability was the most frequently reported quality attribute (18 studies), followed by reliability, efficiency, and usability (5 studies). The authors concluded that "the coverage of quality attributes is wide, but with a predominance of product quality attributes over quality in use attributes" [23]. Our findings confirm these results, however, the scope and the study design differs.…”
Section: Related Worksupporting
confidence: 85%
See 1 more Smart Citation
“…Maintainability was the most frequently reported quality attribute (18 studies), followed by reliability, efficiency, and usability (5 studies). The authors concluded that "the coverage of quality attributes is wide, but with a predominance of product quality attributes over quality in use attributes" [23]. Our findings confirm these results, however, the scope and the study design differs.…”
Section: Related Worksupporting
confidence: 85%
“…Goulão's work [23] reported a tertiary study about quality in model-driven engineering. They identified 22 systematic literature reviews and mapping studies that report quality attributes in the context of MDE, from 2008 to 2015.…”
Section: Related Workmentioning
confidence: 99%
“…Their main goal is to improve developers’ productivity as well as reducing the communication gap in software development between programmers and domain experts [ 24 ]. Moreover, DSLs are considered increasingly popular software development techniques, that use concepts from the problem domain rather than the solution domain [ 25 ].…”
Section: The Aggir Grid Model and Dslmentioning
confidence: 99%
“…Unlike other reviews on the same topic (most of which are summarized in (Goulão et al, 2016)), we focus on the identification of explicit definitions of quality for MDE, as well as the perception of quality in model-driven projects from real practitioners and its associated support in the academic/research field. This focus is important considering that, in the Engineering field, high quality is determined through an assessment that takes an artifact under evaluation and checks whether or not it is in accordance with to its specification (Krogstie, 2012c).…”
Section: Introductionmentioning
confidence: 99%